Respiratory Rehabilitation for Post-Covid-19 Patients - A. G. Malyavin; S. L. Babak; M. V. Gorbunova (SINAPS LLC, 2021)
In the presented clinical review, we evaluated the possibilities of drug and non-drug strategies for eliminating and preventing pathophysiological changes in the respiratory system of post-COVID-19 patients. We offer up-to-date rehabilitation algorithms based on the assessment of the severity of clinical manifestations of COVID-19, the possibilities of rehabilitation techniques and the patient's personal compliance with their implementation.